Involvement of the sensorimotor system in less advanced L2 processing: Evidence from a semantic category decision task - Bai, Yating; He, Wenguang (Frontiers in Psychology, 2022)
Increasing evidence indicated that the sensorimotor system involved in advanced L2 processing, what does sensorimotor information play in the course of less advanced L2 comprehension? In the current study, two experiments were carried out using the lexical decision task (LDT) and semantic category task (SCT). The results showed that, in LDT, a task more likely to make judgments based on physical properties (e.g., familiarity, orthography) of words, “up-pointing” words not resulted in faster upward than downward responses, and “down-pointing” words also not resulted in faster downward than upward responses, while in SCT, compatibility effects were found, specifically, searching the up target after “up-pointing” words were faster than after “down-pointing” words and searching the bottom target after “down-pointing” words were faster than after “up-pointing” words. Hence, we concluded that L2 sensorimotor association, at least for L2 with low proficiency, was not automatic in nature and was dependent upon deeper semantic task demands.